A Study on the Documentation and Analysis of the Urban Acoustical Environment in Terms of Soundscape - Ozcevik, Asli; Can, Zerhan Yuksel (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2012)
Soundscape is a relatively new concept that defines the acoustical environment by the interaction of multiple sound sources and environmental parameters. Soundscape concept treats the sound environment as a multi-dimensional entity, based on the complex interaction between sound source, physical environment and human beings. A method for documenting the sound environment based on sound recordings provides qualitative data while the quantitative data is supplied by conventional acoustic measurements. Acoustical perception; in other words, how a person perceives the sound, is the subject focused on in this method. The review of the related literature shows that there is not a common agreement on t the properties of the subjective and objective data, the methods of data collection and evaluation, or the statistical methods to be used in the correlation. Therefore, a wide-frame study aiming to develop an approach based on soundscape for the evaluation, conservation and rehabilitation of acoustical comfort in urban areas, has been planned and realized. The process followed in this study, on documenting and analyzing the sound environment via sound recordings is presented in this article. Accordingly, the method of deriving the sound recordings which refer to the actual sound environment and confirming their quantitative and qualitative accuracy, are described through field work.
Keywords: Soundscape; sound recording; urban acoustical environment; Architecture